Nuclear Magnetic Resonance and X-ray Crystallography to Improve Struvite Determination. (2nd November 2017) - Witty, Michael; Dingra, Nin N.; Abboud, Khalil A.; Felts, Ashley C.; Ayudhya, Theppawut Israsena Na
ABSTRACT: Ammonium and phosphate removal from industrial streams is important for many chemical processes, especially wastewater and sewerage treatment. Struvite precipitation is a popular choice and has been well characterized in model systems. However, struvite is a member of a family of similar phosphates of various valences and degrees of hydration. This paper shows that the ammonium phosphate precipitation from complex waste of decaying urine is identical to the product in model and other organic systems, i.e., struvite. We have shown that titration assays are possible for struvite, but they are difficult and hence we have also used nuclear magnetic resonance (NMR) and X-ray crystallography. NMR shows the high purity of struvite. Surprisingly, the crystals from this system are large and generate improved structural determination by X-ray crystallography compared to struvite prepared in solution or discovered in other natural systems. These large crystals allow facile separation of struvite, compared to more conventional methods using fluidized bed reactors which generate irregular concretions with difficulty.